Transformasi Digital Umkm Sebagai Strategi Inovasi Dan Peningkatan Daya Saing Di Era Industri 4.0 - Rudi Kurniawan; Tati Suprapti; Achmad Fikri; Aditia (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Micro, Small and Medium Enterprises (MSMEs) play a crucial role in the local economy, but often face challenges in marketing and financial management. Lack of knowledge and skills in marketing strategies and accounting leads to limited market reach and lack of efficiency in business management. This research aims to empower MSMEs through digital transformation to increase innovation and competitiveness in the industry 4.0 era. The methods used in this research include training on digital marketing and technology-based accounting systems for MSME players in Tarikolot District. The results show that the application of digital technology, such as online marketing and the use of accounting applications, can improve business efficiency and expand the MSME market. With digital transformation, MSMEs are more adaptive to changing market trends and able to compete with larger businesses. This study confirms that support in the form of education and technology implementation is essential to sustainably improve the competitiveness of MSMEs.